2002
DOI: 10.1093/jac/49.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and evolution of resistance to quinolones in Escherichia coli after prolonged administration of ciprofloxacin in patients with prostatitis

Abstract: The emergence and evolution of quinolone-resistant Escherichia coli in faeces of patients with prostatitis treated with high-dose oral ciprofloxacin for 1 month were studied. In 11 of 23 patients, from whom only quinolone-susceptible E. coli was isolated before treatment, quinolone-resistant strains, genetically distinct from the quinolone-susceptible ones, predominated during and just after therapy. Two months after treatment, these were completely displaced by quinolone-susceptible E. coli, genetically disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 9 publications
1
31
2
1
Order By: Relevance
“…These data are consistent with several studies of healthy human volunteers in the community that demonstrated that de novo emergence of resistant gram-negative bacilli may be uncommon during fluoroquinolone monotherapy regimens (8,9,21). However, frequent emergence of fluoroquinolone-resistant gram-negative bacilli has been ob-served in some community studies and in many studies in health care facilities (2,3,11,12,(14)(15)(16)(17)(18)(20)(21)(22). Factors such as repeated exposures or preexisting colonization with resistant gram-negative organisms could contribute to more frequent acquisition of resistant gram-negative bacilli in these studies.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…These data are consistent with several studies of healthy human volunteers in the community that demonstrated that de novo emergence of resistant gram-negative bacilli may be uncommon during fluoroquinolone monotherapy regimens (8,9,21). However, frequent emergence of fluoroquinolone-resistant gram-negative bacilli has been ob-served in some community studies and in many studies in health care facilities (2,3,11,12,(14)(15)(16)(17)(18)(20)(21)(22). Factors such as repeated exposures or preexisting colonization with resistant gram-negative organisms could contribute to more frequent acquisition of resistant gram-negative bacilli in these studies.…”
supporting
confidence: 88%
“…Numerous studies have demonstrated that fluoroquinoloneresistant gram-negative bacilli may emerge during treatment with fluoroquinolone antimicrobial agents (2,3,11,12,(15)(16)(17)(18)(20)(21)(22). Because the fluoroquinolones differ significantly with regard to the amount of intestinal excretion and in vitro activity against anaerobic bacteria (8,9,21), it is plausible that they may differ in their propensity to promote colonization with fluoroquinolone-resistant gram-negative bacilli.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have been limited by focusing on only patients with specific chronic conditions (e.g., cancer or prostatitis) or patients who reside in long-term-care facilities (1,8,9,11), including only subjects receiving FQ therapy (1, 9, 11), and utilizing infrequent fecal sampling (i.e., Ն1-month intervals) (8, 11). Furthermore, the impact of FQ resistance phenotype and/or genotype on duration of colonization has not been studied.…”
mentioning
confidence: 99%
“…There are three possible interpretations of this finding: (i) unmasking of fluoroquinolone-resistant organisms present in low numbers before therapy but undetected by the methodology; (ii) acquisition of an exogenous, resistant strain during treatment; and (iii) selection in the host of highly resistant mutations from pre-existing, intermediately susceptible organisms. 17 Second, the data from our study suggest that therapy protocols should be adequately differentiated with regard to the different ultrasound patterns observed before and after antibiotic therapy. In particular, it would be important to evaluate or to subject to a longer duration of therapy forms limited to ultrasound complications or to add other standard therapies to the antibacterial treatment; in fact, with regard to the treatment of infertility, antibiotics play a role in bacterial prostatitis, whereas in abacterial prostatitis, other treatments, such as antioxidant compounds, sacral nerve stimulation and antiinflammatory treatments, are worth being considered.…”
Section: Discussionmentioning
confidence: 78%